KANDUNGAN BAKTERI COLIFORM PADA AIR SUMUR TIDAK BERDINDING SEMEN DAN AIR SUMUR BERDINDING SEMEN - Novianti, Dewi; Suryani, Suryani (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2011)
ABSTRACTWater Well represent one of the source of clean water which still used many by Indonesia society. Water Well earn terkontaminasi porosity so that have natural potency to degradation of quality effect of ugly sanitasi, like existence of porosity irrigate household waste and of irrigate from less permanent tank septik. Wall well not cement and well have cement wall to influence porosity of tank septik. Quality ofwell water can be seen from its bacterium content of it. The research aims to know difference of bacterium content of coliform at wall well water not cement and well have cement wall. Research use presumptive test and confirmed test of coliform bacteria, and do analysed to use t-test. Result of research show there are difference of obstetrical signifikan coliform bacteria at wall well water not cement with well water have cement wall. At wall well water have not cement is have coliform bacteriamore.Key words: Coliform bacteria, wall well water not cement, well have cement wall.